Language Barrier in Disease Terminologies Used by Cattle Rearers and Veterinary Extension Workers in Yola, Adamawa State, Nigeria - Adamu, Husaini; Iliyasu, Usman Bobbo (Journal of Natural Language and Linguistics, 2025)
Language is fundamental to a person’s behavior. It allows the person to express opinions, share feelings, tell stories, and communicate complex messages and knowledge. Language is our greatest facilitator that allows us to share and understand each. It can be seen as a system of abstract codes that allows individual to communicate, and also provides them with significant structure of suggestions and a relational background that maintains identities. This study is concerned with how terms are used by two communities related with Animal husbandry. On one hand, there are the cattle rearers, and on the other hand the veterinary extension workers who visit the rearing community for the purposes of vaccination and providing advice, etc. The Ethnographic research design, therefore, is selected for the study; this research design is a qualitative research procedure for describing culturally shared groups in terms of beliefs, patterns of their behavior and language. This design is adopted because ethnographers normally study cultural ideas drawn from cultural anthropology. They do not just go into the field looking for anything that comes their way; rather they are going there to venture on how they can add knowledge about culture. This study, therefore, looks for shared behaviors, beliefs, and language in the culture-sharing group of the Fulani cattle rearers and the veterinary extension workers. Since the data reflects the community, most of the data were collected from the participants selected in order to help the researchers understand the cultural group better. Much time has been spent with the participants, because questionnaire will not give much information needed due to Language obstacle. Focus Group discussion therefore was used for this study. This is a form of group interview in which a small group, the participants in a structured discussion of a topic of interest. The findings of the study were discussed and some suggestions were made